2014
DOI: 10.1016/j.eplepsyres.2014.09.002
|View full text |Cite
|
Sign up to set email alerts
|

An interictal EEG spectral metric for temporal lobe epilepsy lateralization

Abstract: Objective Visually-obvious abnormalities in the resting baseline EEG – slowing, spiking and high-frequency oscillations (HFOs) - are cardinal, though incompletely understood, features of the seizure onset zone in focal epilepsy. We hypothesized that evidence of cortical network dysfunction in temporal lobe epilepsy (TLE) would persist in the absence of visually-classifiable abnormalities in the baseline EEG recorded within the conventional passband, and that metrics of such dysfunction could serve as a lateral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 27 publications
2
6
1
Order By: Relevance
“…Although we did not observe difference of spectral power between the two groups that reach statistical significance, a tendency for decrease of delta power in areas (ROI 6) in seizurefree patients compared to ones with persistent seizures. A previous study on EEG free from visual abnormality showed difference of spectrum-based metrics between TLE and healthy subjects [19]. Because interictal lesional slowing is related with epileptic network in TLE patients [20], our data suggest that still remaining abnormal network is related with recurrence of seizures.…”
Section: Discussionmentioning
confidence: 47%
“…Although we did not observe difference of spectral power between the two groups that reach statistical significance, a tendency for decrease of delta power in areas (ROI 6) in seizurefree patients compared to ones with persistent seizures. A previous study on EEG free from visual abnormality showed difference of spectrum-based metrics between TLE and healthy subjects [19]. Because interictal lesional slowing is related with epileptic network in TLE patients [20], our data suggest that still remaining abnormal network is related with recurrence of seizures.…”
Section: Discussionmentioning
confidence: 47%
“…We have demonstrated previously (Kalamangalam et al, 2014a; Kalamangalam et al, 2014b; Kalamangalam and Slater, 2015) that such a formalism for the EEG and ECoG – a continuum hypothesis, though not necessarily restricted to a particular distribution – naturally lends itself to the emergence of large-scale synchronous (i.e., epileptic) activity. Synchronization involves the oscillators ‘condensing’ to a smaller distribution by increasing their mutual coupling, leading to the appearance of large amplitude coherent rhythms in the time domain as the coupling parameters cross a threshold.…”
Section: Resultsmentioning
confidence: 92%
“…The log-normal model is a continuum approximation in frequency space: the ECoG is viewed as a collection of oscillators whose frequency distributions (via a combination of intrinsic frequencies and other frequencies arising from self-interaction) approximate that statistical distribution. We have demonstrated previously (Kalamangalam et al, 2014a; Kalamangalam et al, 2014b; Kalamangalam and Slater, 2015) that such a formalism for the EEG and ECoG – a continuum hypothesis, though not necessarily restricted to a particular distribution – naturally lends itself to the emergence of large-scale synchronous (i.e., epileptic) activity. Synchronization involves the oscillators ‘condensing’ to a smaller distribution by increasing their mutual coupling, leading to the appearance of large amplitude coherent rhythms in the time domain as the coupling parameters cross a threshold.…”
Section: Resultsmentioning
confidence: 92%
See 2 more Smart Citations